Masculinity and alcohol in postfeminist popular culture : teenage boys consume music videos : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University, Wellington, NZ - Lindsay, Samuel (Massey University, 2015)
Within a highly liberalised New Zealand market, excessive alcohol consumption by young men remains concerning for its relation to a raft of poor health and social outcomes. Various media formats construct alcohol consumption as desirable through gendered discourses, particularly the music video. Music videos are easily accessible through online platforms, are aimed at teenage audiences, and are increasingly linked to the alcohol industry. This research explored first, how masculinity and alcohol consumption are constructed within four mainstream pop music videos and second, how young teenage boys talk about these music videos after viewing them. Critical multi modal discourse analysis was employed to analyse the lyrics, music and visual content of the music videos, and discourse analysis to examine the talk of eleven boys, aged 13-14. The boys were recruited from a co-educational urban secondary school in New Zealand. The videos constructed discourses of provision, extreme consumption, and various forms of freedom and together they offered specific subject positions, including the playboy and female objectification. These findings are discussed in terms of post-feminist capitalist culture and hegemonic masculinity. The teenage participants took up the discourses constructed in the videos but in both resistant and accepting ways. They drew on discourses of enjoyment, animalistic/biological, feminist, and moral/ health discourses, and employed several discursive strategies to position themselves as critics of the popular culture that the videos represented. However, discrepancies and contradictions within the boys’ responses were found. These included the use of a ‘slut’ discourse, as well as a discourse of women’s enjoyment, to accept the objectification of women in the videos. Although the participants largely rejected alcohol as bad through a moral/ health discourse, certain acceptances of the artists’ authenticity, the videos’ visual content, and minimisations of alcohol content suggested ways in which alcohol might be accepted. The findings are analysed and discussed in relation to issues of post-feminism and hegemonic masculinity theory. Potential future directions and implications are explored, such as more sophisticated media interventions targeted at the complex ways in which powerful post-feminist and hegemonic discourses obscure their operations.
Keywords: Teenage boys; Alcohol use; Music videos; Social aspects; Women in popular culture; New Zealand